SENSIBILIZAÇÃO PARA A LEITURA LITERÁRIA: MEDIAÇÃO DOCENTE, LIMITES E POSSIBILIDADES NO CONTEXTO DE SÃO JOÃO DO PARAÍSO - MA - Abreu, Jemima Marinho (Universidade Federal do Tocantins, 2022)
The present research consisted of reflecting on the formation of literary readers in the context of São João do Paraíso - MA. To this end, we sought to analyze the teachers' understanding of the challenges and possibilities in provoking/promoting the experiences of literature and delimited as a field of analysis the initial years of Elementary School in the schools of the aforementioned municipality. Coupled with this objective, we also discuss the benefits of literature in human development, justifying it as a fundamental right, we establish horizons between the literary training of the teachers who were part of the research and the teaching methods, by identifying in this process, strategies for approaching the literary book and teacher mediation in the school environment. We are based on the thinking of Abramovich (1997), Candido (2011), Colomer (2007), Martins (1994), Silva (2008 and 2009), Cosson (2009) and many others. We start from the qualitative-quantitative approach and have as theoretical-methodological principles the bibliographic research and researches through surveys. In order to obtain the data, several factors led us to choose to apply a poll virtually, via Google Forms, whose questions were about the teachers' general information: professional profile and literary training; literature in the school territory. Through this research instrument, it was possible to obtain the feedback of 14 teachers from the early years of elementary school in urban schools in the municipality of São João do Paraíso - MA. The participants' responses provided a rich debate on the formation of literary readers, and showed an encouraging scenario with regard to the strategies used by reading mediators, as well as denouncing the main obstacles to the development of teaching methods. Finally, the research allows us to conclude and forecast that the promotion of reading, the formation of literary readers and the formation of reading mediators are a long way to go and must be a constant working subject. In this sense, we emphasize that within this content there were other concerns that can be explored in further research.